A Survey on Quality of Service in the Voice Over IP Technology - Homero Toral Cruz; José Luis Vázquez Ávila; Rafael Sánchez Lara; Joel Antonio Trejo Sánchez; J.A. Alvarez Chavez (European Scientific Journal, ESJ, 2019)
Voice services can be transmitted by circuit switched and packet switched networks (Internet). Voice over Internet Protocol (VoIP) is one of the most attractive and important service in telecommunication networks, current implementations of VoIP have two main types of architectures, which are based on H.323 and Session Initiation Protocol (SIP). However, when the voice traffic is transported over Internet, the packet based transmission may introduce impairments and it has influence on the Quality of Service (QoS) perceived by the end users. The voice quality of VoIP systems depends on many QoS parameters. Particularly, One Way Delay (OWD), jitter and Packet Loss Rate (PLR) have an important impact on voice quality. This survey presents the main concepts relating to the VoIP technology and quality of service issues.